Genetic structure and divergence of marginal populations of black poplar (Populus nigra L.) in Poland - Weronika Barbara Żukowska; Andrzej Lewandowski (Scientific Reports)
Abstract Genetic diversity is crucial to secure the survival and sustainability of ecosystems. Given anthropogenic pressure, as well as the projected alterations connected with the level and circulation of water, riparian forests are of particular concern. In this paper, we assessed the genetic variation of black poplar – one of the keystone tree species of riverine forests. The natural habitats of black poplar have been severely transformed leading to a significant decline of its population size. Using a set of 18 nuclear microsatellites and geographic location data, we studied 26 remnant populations (1,261 trees) located along the biggest river valleys in Poland. Our main goal was to assess the overall genetic variation and to verify if range fragmentation and habitat transformation have disrupted gene exchange among populations. Genotyping revealed that 261 trees were clones. The level of clonality was higher in more transformed river sections. All populations have probably gone through a drastic genetic bottleneck in the distant past, and most of them have low effective population sizes. Still, the overall level of genetic variation remains high, but certain populations require attention due to their lower genetic variation, higher clonality and strong spatial genetic structure. Genetic differentiation was low, yet Bayesian clustering supported the existence of 11 genetic clusters. According to the results, gene exchange is most prevalent between adjacent populations. Relatively free gene flow occurs only along the Vistula, particularly in its middle section which is characterized by the highest genetic variation. Noticeable genetic structuring was observed along the Oder. Populations located at the range margin showed signs of genetic divergence and reduction of variation. We conclude that human activities have impacted the gene pool of black poplar in Poland by disrupting landscape connectivity and preventing the species from generative reproduction. The study provides practical guidelines on how to develop and implement the conservation program for the gene pool of black poplar in Poland. It also presents a strong case favoring river renaturation and genetic monitoring, particularly concerning keystone species.